2011
DOI: 10.1039/c0em00706d
|View full text |Cite
|
Sign up to set email alerts
|

Soils and sediments of the Thua Thien-Hue Province (central Vietnam): recognizing trace element sources and the likely influence of natural events

Abstract: Trace element concentrations have been measured in soil and sediment samples taken from the Thua Thien Hue (TT-H) Province and the Tam Giang-Cau Hai (TG-CH) Lagoon in 2002 and 2004. Results show that the lagoon is only slightly contaminated by elements such as Ag, Cd, Cr, Cu, Ni, Pb and Zn, whereas As, probably naturally enriched in this Asian region, reaches values above the lowest internationally accepted sediment quality guidelines. Concentrations in soils are ascribable to natural sources and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…210 Pb profiles ( layers and remained relatively constant downcore. TN differed slightly from this pattern owing to higher values at depth as previously described [27], and values at NM showed large oscillations in the deep levels. The values obtained from 2008 samples span between 0.37 (NN) and 0.78 (CR) and the depth profiles show differences, especially at NM and CR.…”
Section: Sediment Featuressupporting
confidence: 47%
See 3 more Smart Citations
“…210 Pb profiles ( layers and remained relatively constant downcore. TN differed slightly from this pattern owing to higher values at depth as previously described [27], and values at NM showed large oscillations in the deep levels. The values obtained from 2008 samples span between 0.37 (NN) and 0.78 (CR) and the depth profiles show differences, especially at NM and CR.…”
Section: Sediment Featuressupporting
confidence: 47%
“…Porosity-depth profiles were used as independent information to check the best correspondences. Giuliani et al [27] found that replicate samples were characterised by similar trends of 210 Pb and porosity, especially in the topmost sections. On this basis, and assuming of constant 210 Pb supply in the topmost levels, a good superimposition was observed when the profiles from 2008 cores were transposed downward (as in Figure 2) to find the best overlap.…”
Section: Comparison Of 210 Pb Activity and Porosity Depth Distributiomentioning
confidence: 97%
See 2 more Smart Citations
“…As final repositories of materials coming from land, atmosphere, and overlaying water masses, sediments deposited under low-energy conditions are important in environmental studies as they give a trustworthy picture of both present and past situations (e.g., Frignani et al, 2004;Giuliani et al, 2011a;Bellucci et al, 2012). In addition, they provide information on the chronology of contaminant inputs when conditions of low sediment perturbation are met.…”
Section: Introductionmentioning
confidence: 99%